Indigenous Publicity in American Public Lands Controversies: Environmental Participation in the Fight for Bears Ears National Monument - Johnson, Taylor N. (Frontiers in Communication, 2021)
Environmental decision-making scholars have attended closely to the role of publicity publics and counterpublicity counterpublics in environmental controversies. However, this body of work has undertheorized the ways that Indigeneity may complicate access to or desirability of American publicity”public good” as a driving force in environmental advocacy. Inclusion within the American national body both functions as an advocacy tool for Native people and as a colonial discourse that may undermine sovereignty goals. Through a critical rhetorical analysis of documents at the center of the controversy over Bears Ears National Monument, this essay explicates the deployment of American publicity both to support and to undermine Native advocacy for the Monument. Scholars of rhetoric and environmental decision-making must re-orient toward publicity in a way that accounts for settler colonialism and decolonization.